Determination of Factors Influencing Mothers in Developmental Stimulation Toddler Children in Pondok Udik Village : Determinasi Faktor yang Mempengaruhi Ibu dalam Stimulasi Perkembangan Anak Usia Toddler Di Desa Pondok Udik - Rahmat Kurniawan; Andin Restu Marsiwi; Nurul Maulidah; Novica Ariyanti Putri; Nurmiaty Nurmiaty (Salando Health Journal, 2025)
Stimulation of children's growth and development includes fine motor development, gross motor skills, speech and language development, and independence. The toddler age is the right time to optimize children's development. For children's development to be optimal, the basic needs of children for growth and development must be met first. Various problems in child development, such as motor delays, language, and behavior. Children who receive directed stimulation will develop faster than children who receive less stimulation or no stimulation at all. The purpose of the research was to determine the relationship between stimulation of maternal knowledge, stimulation of maternal attitudes, and maternal family support with stimulatory behavior. The research design used a cross-sectional approach. The research location in Pondok Udik Village involved 67 respondents using purposive sampling techniques. The statistical test obtained a value of ρ 0.020 <α = 0.05 meaning that there is a relationship between the stimulation of the mother's knowledge and stimulatory behavior, the value of ρ 0.030 <α = 0.05 means that there is a relationship between the stimulation of the mother's attitude and the results of the statistical test obtained a value of ρ 0.017 < α = 0.05 meaning that there is a relationship between the mother's family support and stimulatory behavior. The study's results showed a relationship between family knowledge, attitudes, and support and stimulatory behaviors carried out by mothers. There is a need for community-based interventions such as regular education, parenting training, and mothers' group support to increase the capacity of families to provide appropriate and sustainable development stimulation to children.